Synthesis of N2-glycosylated Dihydropyrimidones – A Novel Approach Using Epoxy Sugar - R. Subimol, K.; Arul Antony, S. (Letters in Organic Chemistry, 2017)
Background: A novel route towards synthesis of N-glycosylated dihydropyrimidones (DHPMs) using epoxy sugar has been described. The DHPM derivatives were synthesised from aromatic aldehydes, urea/thiourea and ethyl acetoacetate in presence of CuCl and BF3.OEt2. The reported methodology of glycosylation of DHPMs is of synthetic importance and can overcome traditionally utilized multistep synthesis of N-glycosylated heterocycles. The proposed economical and convenient methodology can open new pathways to generate biologically important glycosylated molecules. The dihydropyrimidone derivatives and their corresponding glycosides were characterized using 1H, 13C NMR and elemental analytical methods. Methods: The compounds were purified via coloum chromatography using hexane/ethylacetate as solvent. Thin-layer chromatography (TLC) was performed on manually coated plates (Acme) with detection by UV light or iodine vapour. Column chromatography was performed using SiO2 (Acme 100-200 mesh). NMR spectra were recorded with Bruker Avance 300 (300 MHz) using tetramethyl silane as internal solvent. The solvent peak in 1H NMR and 13C NMR was adjusted to 7.5 and 77.23 ppm for CDCl3. Elemental analysis was carried out using Eager 300 C, H, N analyzer at IIT Bombay (Mumbai, India). Results: A series of structurally divergent dihydropyrimidones have been synthesised using aromatic aldehydes, urea/thiourea and ethyl acetoacetate in dry THF catalysed by Cu (I) and BF3.OEt2. Traditionally, N-glycosylation of heterocycles proceeds either via partial protection of saccharide moiety and (or) selective protection of active centres present in the heterocycle species using silyl protecting groups. Here we attempted to overcome the conventional methodology of selective protection of heterocycles by utilizing epoxy sugars derived from tri-O-acetyl glucal. Among the screened catalyst, sodium hydride was the potential catalyst and acetonitrile, acts as the prime solvent for N-glycosylation of DHPMs. The increased yield in the presence of acetonitrile and sodium hydride is due to its increased polarity leading to the greater ion-dipole interaction which thereby stabilizes the deprotonated DHPM and results in the expected product under favourable mild reaction conditions. Though both N1 and N3 of cyclic urea are susceptible for glycosylation; however, the steric and resonance stabilization leads to the favourable β-glycosylation at N1. Conclusion: The reported N-glycosylation methodology is an alternative pathway for N-glycosylation of heterocyclic moieties. Moreover, this novel methodology will open insights in understanding N-glycosylation reactions of structurally rigid and multifunctional heterocyclic molecules.
Keywords: dihydropyrimidone-N-glycosides